Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Robert I. Cecil, December 31, 1988 - Cecil, Robert I.et al (1988)
Iowa Christmas bird counts of species found in Keokuk (Iowa, Illinois, Missouri) contributed by Robert I. Cecil, December 31, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed